Grupos finitos cujos subgrupos abelianos satisfazem a propriedade de interseção trivial - Danilo Sançao da Silveira (2012)
A subgroup H of a group G is called a TI-subgroup of G if HHx = 1or H for all x G. A group G is called a ATI-group if every abelian subgroup of G is a TI-subgroup. In this text we classify the finite ATI-groups, based on reference [8] in the bibliography